A Bibliometric Multicriteria Model on Smart Manufacturing from 2011 to 2018. Issue 11 (2018) - Felice, F. De; Petrillo, A.; Zomparelli, F.
Abstract: This study reviews the academic literature on Smart Manufacturing from the industry perspective. The methodological approach combines bibliometric analysis and multi criteria decisionmaking models. Firstly, the paper aims to identify the most relevant topics on Smart Manufacturing. Secondly, it aims to weigh them and to define their interdependences. The initial sample consists of 1.498 articles published between the 2011 and 2018. The semi-qualitative analysis returns an objective numerical result useful to define the predominant area on smart manufacturing applications.